Edukasi Mengenai Penggunaan Saffron Dalam Menurunkan Kecemasan Sebagai Dampak Penggunaan Media Sosial di Siswa SMUN 3 Bantul - sumiyarini, retno; Dias Utami, Khristina; Kusumaningtyas , Kartikadyota (The Journal of Innovation in Community Empowerment, 2024)
Anxiety is the most significant mental problem among adolescents. Several factors trigger the onset of anxiety, including academic aspects, problems with family relationships, characteristics of relation with peers, and the utilization of the internet, especially social media. Some adolescent behaviour occur due to the addiction to playing social media, such as sleep disturbances and sedentary behaviour, which eventually lead to anxiety problems in adolescents. This community service aims to provide adolescents with information about the benefits of saffron to reduce anxiety. The method used in this community service is health education using video media. Fifty-three students of SMUN 3 Bantul participated in this community service, and the result was that the mean knowledge of students regarding the benefits of saffron in reducing anxiety increased significantly (p-value = 0.000). In general, students' knowledge about the benefits of saffron in reducing anxiety increased.